Retinal Microvascular Caliber and Incident Depressive Symptoms: The Multi-Ethnic Study of Atherosclerosis. Issue 5 (15th October 2021) - van Gennip, April C E; Sedaghat, Sanaz; Carnethon, Mercedes R; Allen, Norrina B; Klein, Barbara E K; Cotch, Mary Frances; Chirinos, Diana A; Stehouwer, Coen D A; van Sloten, Thomas T
Abstract: Cerebral microvascular dysfunction may contribute to depression via disruption of brain structures involved in mood regulation, but evidence is limited. The retina allows for visualization of a microvascular bed that shares similarities with the cerebral microvasculature. We investigated the associations between baseline retinal arteriolar and venular calibers (central retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE), respectively) and incident depressive symptoms in the Multi-Ethnic Study of Atherosclerosis (MESA). We used longitudinal data on 4, 366 participants (mean age = 63.2 years; 48.5% women, 28.4% Black) without baseline depressive symptoms. Depressive symptoms, defined as Center for Epidemiologic Studies Depression Scale score ≥16 and/or use of antidepressant medication, were determined between 2002 and 2004 (baseline; MESA visit 2) and at 3 follow-up examinations conducted every 1.5–2 years thereafter. Fundus photography was performed at baseline. After a mean follow-up period of 6.1 years, 21.9% ( n  = 958) had incident depressive symptoms. After adjustment for sociodemographic, lifestyle, and cardiovascular factors, a 1–standard-deviation larger baseline CRVE was associated with a higher risk of depressive symptoms (hazard ratio = 1.10, 95% confidence interval: 1.02, 1.17), and a 1–standard-deviation larger baseline CRAE was not statistically significantly associated with incident depressive symptoms (hazard ratio = 1.04, 95% confidence interval: 0.97, 1.11). In this study, larger baseline CRVE, but not CRAE, was associated with a higher incidence of depressive symptoms.